Assessment of self-medication practice among community pharmacists in Manila, Philippines - Antido, Hanna Rose V.; Bunuan, Danielle C.​,​​; Tuibeo, Louise Mae P.​,​​; Robles, Yolanda R.​,​​ (​​​​​​​​​​Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Many individuals worldwide have been accustomed to this practice and have taken an active role in managing their own health through self-medication. Responsible self-medication can be beneficial to the community especially in countries where there are limited medical services.However,there are several critical issues that must be considered before promoting the potential benefits of this ractice. This study aimed to assess the self-medication practice among community pharmacists in Manila,Philippines. A descriptive, cross-sectional study design was conducted to assess the self-medication practice among community pharmacists using a self-administered questionnaire. Statistical Packageforthe Social Sciences (SPSS) was utilized for data analysis and MS Excel for data encoding. Pearson chi-square was used to determine the correlation of the demographic profile of the respondents to their self-medication practice, frequency and percentage were used to describe the responses of the respondents, p-value of <0.05 was considered significant. Out of the 182 respondents, 145 (79.7%) pharmacists were practicing self?medication the remaining percentage (32.6%) denied the practice of self-medication. Among those who self-medicate,72.4% has familiarity with treatment options, 54.5% reasoned out that their condition does not merit visit to a physician,30.3% avoid health check-up expenses,while 29% respond that they lack time due multiple tasks. The self-medication practice of community pharmacists involved treatment of minor illnesses using OTC medicines, antibiotics,and food supplements. The perceived advantages of self-medication according to the respondents include time saved and cost-effectiveness while for the disadvantages, these include risk of adverse effects and drug interactions, antimicrobial resistance, drug misuse, and polypharmacy. The results of the study showed that community pharmacists still lack knowledge on the concept of self-medication and their roles as a pharmacist in managing the self-medication practice of the public.
Available to the general public.
​​​​​​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, May 2017.
Keywords: Self medication; Drugs, Nonprescription; Antibiotics